Internal Delorme's procedure for rectal outlet obstruction. (27th February 2013) - Ganio, E.; Martina, S.; Novelli, E.; Sandru, R.; Clerico, G.; Realis Luc, A.; Trompetto, M.
Abstract Aim The outcome of the internal Delorme's procedure (IDP) for obstructed defaecation was assessed. Method From October 2001 to March 2009, 167 patients with obstructed defaecation associated with rectal intussusception were operated on. Patients were selected on the basis of validated constipation and continence scores, clinical examination and defaecography. Seventy‐six patients were treated by the IDP alone and 91 patients were treated by the IDP with a levatorplasty. Before surgery and after a mean ± SD follow up of 3.0 ± 1.5 years, patients were assessed using the Cleveland Clinic Incontinence and Constipation Score (CCIS and CCCS), the Obstructed Defecation Score (ODS), faecal urgency and the Patient Assessment of Constipation Quality of Life (PAC‐QoL) questionnaire. Results Seventeen (10.2%) patients developed a postoperative complication including fissure‐in‐ano (4.2%), proctalgia (3.0%), suture‐line dehiscence with stenosis (1.8%) and Clostridium difficile colitis (1.2%). Faecal urgency changed from 22% to 17.6% (P = 0.754). Tenesmus fell from 53.9% to 17.1% (P < 0.001). The CCCS and the ODS fell by 50% or more in 82.6% and 73.7% of the patients, respectively. The CCIS did not worsen significantly in patients who remained incontinent, and 45.7% of the previously incontinent patients regained normal continence. The CCCS decreased from 11 to 3 (P < 0.001) in the patients treated by the IDP and from 12 to 3 (P < 0.001) in the patients treated by the IDP with levatorplasty. The overall recurrence rate was 5.4%. The PAC‐QoL showed a reduction of anxiety/depression and of physical and psychological discomfort (P < 0.001). Conclusion The IDP is an effective and safe option for rectal outlet obstruction caused by rectal intussusception with excellent function and patient satisfaction.